Students‟ Anxiety on Continuous and Comprehensive Evaluation (CCE) at Secondary Schools of Papum Pare District of Arunachal Pradesh - Mondal, Mithun; Doley, Jayanta (International Journal of Psychosocial Rehabilitation, 2020)
The scheme of Continuous and Comprehensive Evaluation (CCE) is an effective tool to enhance the quality of teaching learning processes in the school. The emphasis is now ensuring that every child not only acquire the Knowledge and awareness and skills but also the ability to use these competencies in real life situations. Thus the emphasis is now both on Knowledge and awareness as well as on performance. The CCE or Continuous and Comprehensive Evaluation scheme refers to a school-based evaluation of students that covers all the aspects of a student’s development. Major objectives of this study were i) to find out the level of anxiety of 10th grade secondary school going students on CCE of Papum Pare District of Arunachal Pradesh; ii) to compare the level of anxiety of 10th grade secondary school going students on CCE of Papum Pare District of Arunachal Pradesh in relation to gender variable; iii) to compare the level of anxiety of 10th grade secondary school going students on CCE of Papum Pare district of Arunachal Pradesh in relation to settlement variable. In this study the investigators used descriptive survey method of Educational research. From this study the researcher had found that majority of the secondary school students i.e. (62.50%) shows moderate anxiety level towards CCE after its implementation in the school system of Arunachal Pradesh. From this study it was also found that there is no significant difference between the 10th grade Secondary School students of Arunachal Pradesh on their level of Anxiety on Continuous and Comprehensive Evaluation (CCE) in relation to gender and settlement variable.